973 Regional Paediatric Intensive Care (PIC) Transport Services: Benefits of 2 Becoming 1!. (October 2012) - Lakin, B; Parkins, K; Walker, C; Barber, R; Santo, S; Claydon-Smith, K
Abstract : Background: Approximately 1.7 million children North West and North Wales (UK) and 600–700 are transferred annually from 31 hospitals into 2 regional PICUs. Prior to 2010 specialist PIC transport teams were unit based but review (2007) revealed problems: Minimum 30% PIC transfers by non-specialised teams (associated with adverse incidents) Poor access to clinical advice Delays finding PIC bed Delays mobilising specialist PIC transport team Adverse incidents associated with inexperienced medical personnel (specialist teams) Regional Paediatric Transport Service (NWTS) started 2010 with a single point of contact providing advice, organisation transfer and PIC bed. Methods: Several database audits (first 12 months) to assess quality of retrievals compared to previous data. Results: 91.6% PIC transfers done by NWTS in first year (target > 85%). Retrieval times (median) Mobilisation 29.5mins (pre NWTS 80mins); stabilisation 102 mins (pre NWTS 110mins); total retrieval time 201mins (pre NWTS 310mins) Winter data: consultant present 50% (n=40) retrievals - supporting inexperienced staff. Snapshot (6 weeks) audit showed patient management advice was substantial and potentially avert admission. For example, 13 children were initially referred, but with advice over 3 (median) phone calls (range 2–8) remained in the local centre. Better utilisation PIC beds: refusal rate 5.8% versus 37% pre-NWTS. Satisfaction survey: (referring hospitals) demonstrated overall satisfaction excellent or good in domains including comparison with previous arrangements and clinical care. Conclusions: Our data suggest that improvement in quality has occurred since the launch of NWTS, including improved utilisation of regional PICU beds.